Value logics for service innovation : practice-driven implications for service-dominant logic - Lindhult, Erik; Chirumalla, Koteshwar; Oghazi, Pejvak; Parida, Vinit (Springer, 2018)
Service-dominant logic (SDL) provides a conceptual understanding of and widens the view on value creation in service innovation for product-centric companies. However, empirical research linking SDL and service innovation is still limited albeit expanding. This study provides insights beyond existing discussions on product and service dimensions using the theoretical lens of the value logic perspective. More specifically, the purpose of this study is to examine how value can be understood, targeted, and created in the pursuit of service innovation by product-centric manufacturing companies. Building on a previous investigation of two multinational product-centric manufacturing companies, this paper identifies and develops a theoretical model to describe the space shift in service innovation with four different kinds of value logics, namely, product-based value logic, service-based value logic, virtual-based value logic, and systemic-based value logic. Using a digitalization-driven new service innovation, namely the My Control System, which is a web-based service delivery platform, this paper describes space shifts to enhance value through four value logics as efforts. Further, challenges associated with different value logics are described in terms of complexity traps and service gaps. The study also contributes to bridging the gap between SDL theory and practice by developing a midrange theoretical model for value creation as a specification and amendment to SDL that supports SDL-guided service innovation and servitization in practice.
Keywords: servitization; product-service system; advance services; value co-creation; business model innovation; digitalisaatio; liiketoimintamallit; innovaatiot; fi=Johtaminen ja organisaatiot|en=Management and Organization|